Climatic effects on sow fertility and piglet survival under influence of a moderate climate. (20th May 2014) - Wegner, K.; Lambertz, C.; Daş, G.; Reiner, G.; Gauly, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Although the climate in Germany is moderate, heat stress conditions may occur during summer months. However, it is unknown to what extent sow fertility and piglet survival are affected under moderate climatic conditions in indoor systems. Therefore, this study estimated effects of temperature and temperature–humidity index (THI) on sow fertility and piglet survival under practical husbandry conditions. Temperature and relative humidity were recorded in six piglet-producing farms in Lower Saxony, Germany, from July 2011 to August 2012. Based on that, the THI was calculated. In one farrowing, waiting and servicing unit of each farm two data loggers were installed. Reproductive parameters of 8279 successful inseminations and 10 369 litters including total number of piglets born, liveborn, stillborn and weaned piglets as well as pre-weaning mortality were evaluated. The effects of temperature and THI on reproductive parameters were estimated for varying periods after breeding and before and after farrowing, respectively. Average daily temperature across all units ranged from 15.6°C to 29.0°C, and average THI from 62.4 to 75.1. Season and parity significantly affected total number of piglets born, number of liveborn, stillborn and weaned piglets (P<0.001). The number of piglets born increased with rising temperature and THI in the 1st week post breeding. Higher temperatures and THI values before farrowing resulted in a reduced number of liveborn piglets. Elevated temperature and THI values after farrowing were associated with a greater number of weaned piglets. The pre-weaning mortality significantly decreased with increasing temperature and THI values after farrowing (P<0.05). In conclusion, temperature and THI affected the reproductive performance of the sows and the survival of the piglets in different ways. While increased climatic values at the time of breeding positively affected the total number of piglets born, increased values at the time of farrowing had negative impacts on the reproductive performance of the sows. Piglets benefited from higher temperature and THI values after farrowing.